Sclerotherapy for III- and IV-degree hemorrhoids: Results of a prospective study - Lisi, Giorgio; Gentileschi, Paolo; Spoletini, Domenico; Passaro, Umberto; Orlandi, Simone; Campanelli, Michela (Frontiers in Surgery, 2022)
Background In the last 2 years, anorectal surgery has been strongly affected and even surgery for urgent cases cannot be scheduled; also, patients with III- and IV-degree bleeding hemorrhoids should be treated conservatively. The aim was to evaluate the effectiveness of sclerotherapy in patients who had to postpone surgery. Methods We included all patients with III- and IV-degree bleeding hemorrhoids who underwent outpatient sclerotherapy. The visual analog scale and the hemorrhoid severity score were used at the baseline and at 4 weeks after the procedure with a telephone interview, and all patients were outpatient-evaluated 1 week, 1 month, and 1 year after the treatment. All pre- and postoperative data were recorded. Results From October 2020 to November 2021, 19 patients with III- (12 patients; 63%) and IV-degree (7 patients; 37%) bleeding hemorrhoids were enrolled. The mean operative time was 4.5 min, and no intraoperative complications occurred. One case of tenesmus and three failures were detected. Six months after the procedure, the overall success rate was 84%, although all of the patients enrolled reported persistent bleeding at the end of the study period. Of these, 5 patients (26%) were scheduled for surgery and 11 patients (58%) refused surgery and asked to undergo a re-do sclerotherapy. Conclusion Sclerotherapy with 3% polidocanol foam is a safe and effective procedure also in III- and IV-degree bleeding hemorrhoids. The long-term data on the length of the foam remain to be evaluated in additional studies.